The difference is that evaluating an expression for a given value is an example of let’s say In a example, the variable x is equal to 6 since 6 + 6 = 12. So it means that they are giving you the input already. SOLVING an equation is working backwards, to undo everything that has been done to the input. So you have to do the equation in order to find your answer.
Answer: If the initial term of an arithmetic sequence is a 1 and the common difference of successive members is d, then the nth term of the sequence is given by: a n = a 1 + (n - 1)d The sum of the first n terms S n of an arithmetic sequence is calculated by the following formula: S n = n (a 1 + a n)/2 = n [2a 1 + (n - 1)d]/2
Answer:
Step-by-step explanation:
(x-3)²-4=0
(x-3)²=4=2²
x-3=±2
x=3±2
x=3-2,3+2
x=1,5
it has two distinct roots and a vertex at x=3
Answer:
x= 9/20 = .45
Step-by-step explanation:
20x=9
x= 9/20 = .45